Analysis of Magnetic Field Distribution and Core Loss under Unbalanced Load Conditions using 3D Finite Element Method for 400 kVA Transformer: doi: 10.14456/mijet.2023.18 - Jantanate, Watcharin; Aussawamaykin, Apiwat; Nachaiyaphum, Kwanjai; Pao-la-or, Padej; Bunmat, Arak (Engineering Access, 2023)
The finite element method is a popular methodology used to solve complex problems in engineering according to the specific model of the problem. In this paper, the finite element method was used to analyze the problem of electromagnetic field distribution of power distribution 400 kVA transformers in the form of Maxwell’s equation. The distribution of the resulting magnetic field causes iron core losses and was analyzed under balanced load and unbalanced load conditions. The result analysis was developed according to the 3D finite element method and modeled by the MATLAB program. It can be seen that grain-aligned silicon steel has less loss in the steel core than M5-grad silicon steel.